Predicting Academic Success of Junior Secondary School Students in Mathematics through Cognitive Style and Problem Solving Technique - Badru, Ademola K. (NIU Journal of Humanities; Vol 3 No 1 (2018): KIU Journal of Humanities, Vol. 3 No. 1, March 2018, 2018)
This study examined the extent of prediction of academic success of Junior secondary school Mathematics students using their cognitive style and problem solving technique with the three hypotheses formulated.  A descriptive survey type was adopted. A purposive sampling procedure was used to select five Public Junior secondary schools and an arm of intact class students were selected from each selected school. Three instruments were used as Sigelâ€™s Cognitive Style Test (SICOST), Problem Solving Technique Test (PSTT) and Mathematics Achievement Test (MAT). Their content validity values were 0.79; 0.74 and 0.84 respectively using Lawshe method. And reliability values were 0.82, 0.79 and 0.87 of SICOST, PSCT and MAT respectively. The results of the Multiple regression test show that: the studentsâ€™ cognitive style and problem solving technique jointly significantly predicted academic success in Mathematics (F (2,147) = 3.99; P < 0.05) and the relative contribution of each of the predictor variables (the beta values of the problem solving technique and cognitive style) are 0.16 and 0.15 respectively to prediction.  However, the implications and conclusion were made. Keywords:  Academic success, Cognitive style, and Problem solving technique